PERENCANAAN STRATEGIS SISTEM INFORMASI MENGGUNAKAN METODE WARD AND PEPPARD PADA PT. CENTRAL BEARINDO INTERNATIONAL - Vionetha Lavega; Monalisa Effendy; Niko Ananda Limmanto; Mario Aldy Wijaya; Darren Hansen; Mulyati Mulyati (Jurnal Riset Sistem Informasi, 2026)
The rapid development of information technology requires companies to implement strategic planning of Information Systems/Information Technology (IS/IT) that is aligned with business objectives. PT Central Bearindo International, a national-scale bearing distribution company, has utilized several information systems to support its operational activities; however, these systems still operate independently, resulting in data integration issues and reduced operational efficiency. This study aims to develop an IS/IT strategic planning framework that effectively supports the company’s business needs. The Ward and Peppard method is employed, encompassing internal and external business environment analysis, IS/IT condition analysis, application portfolio mapping using the McFarlan Strategic Grid, and the formulation of IS/IT development recommendations and a roadmap. The results indicate that the company requires integration of sales, inventory, and financial systems to improve data accuracy and consistency. Furthermore, optimization of existing systems and the development of a human resource (HR) module integrated with the fingerprint-based attendance system are recommended to enhance operational efficiency. The integrated utilization of system data is also expected to support more accurate and data-driven managerial decision-making. This study is expected to serve as a reference for companies in developing integrated information systems aligned with their business strategies.